Enhancing the Optical Efficiency of Near-Eye Displays with Liquid Crystal Optics - Tao Zhan; En-Lin Hsiang; Kun Li; Shin-Tson Wu (Crystals, 2021)
We demonstrate a light efficient virtual reality (VR) near-eye display (NED) design based on a directional display panel and a diffractive deflection film (DDF). The DDF was essentially a high-efficiency Pancharatnam-Berry phase optical element made of liquid crystal polymer. The essence of this design is directing most of the display light into the eyebox. The proposed method is applicable for both catadioptric and dioptric VR lenses. A proof-of-concept experiment was conducted with off-the-shelf optical parts, where the light efficiency was enhanced by more than 2 times.